Effect of maternal investments on the offsprings, in special respect to the influence of stress in birds: Irodalmi áttekintés - Szőke, Zsuzsanna; Péczely, Péter; Barna, Judit (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
nvestigations on avian maternal effects, supporting the offsprings during hatching goes back only to 15 years. One of the important biological accomplishments from the last decade was the appearance of researches on the role of various hormones in the adaptive interpretation of supraindividual patterns surpassed the physiological examination on infraindividual hormonal milieu. Authors first review the effect of maternal stress on the in utero developing embryo and the postnatal development, which have been under examinations for a rather long time in mammals. Shortly show the similar progresses in reptiles and fish. The main task of the review is to analyse the physiological role and the supraindividual interpretations of the steroid hormones deponated into the yolk of birds. The effects of yolk androgenes, the 17-beta-estrogen and corticosterone on the embryonic and postnatal development of the offspring is detailed adverting to the effect of stress on the egg size and modified sex ratio by yolk steroids.
Keywords: maternal stress; embriogenesis; steroid hormones; birds